Structures of the rat complement regulator CrrY - Roversi, Pietro (International Union of Crystallography, 2011)
Complement receptor 1-related protein Y (CrrY) is an important cell-surface regulator of complement that is unique to rodent species. The structure of rat CrrY domains 1–4 has been determined in two distinct crystal forms and reveals a 70° bend between domains 3 and 4. Comparisons of this structure with those of other complement regulators suggests that rearrangement of this interface may occur on forming the regulatory complex with C3b.